The Anti-angiogenic Effect of Chlorogenic Acid on Choroidal Neovascularization - Kim, Cinoo (The Korean Ophthalmological Society, 2010)
PURPOSE: To evaluate the inhibitory effect of chlorogenic acid on laser-induced choroidal neovascularization (CNV) in a rat model. METHODS: Intraperitoneal injection of chlorogenic acid (10 mg/kg) was inititated one day prior to laser photocoagulation and continued for eight days. Eyes were removed 14 days after laser photocoagulation. Fluorescein angiography was employed at seven and 14 days to assess the CNV lesions, and histological examination was performed. Quantification of CNV size and leakage were performed both in histological sections and fluorescein angiography in order to compare the inhibitory effects of chlorogenic acid on CNV with the results of the control. RESULTS: Histological analysis showed no significant difference in CNV size between the treated and control groups. However, CNV leakage on fluorescein angiography had significantly decreased in the chlorogenic acid-treated group at 14 days after laser photocoagulation compared with that of the control group. In addition, CNV size on fluorescein angiography had significantly decreased in the treated group at seven and 14 days. CONCLUSIONS: These results suggest that chlorogenic acid has anti-angiogenic effects on CNV and may be useful as an inhibitor in the treatment or prevention of neovascular age-related macular degeneration.